Relationships among organizational culture, open innovation, innovative ecosystems, and performance of firms: Evidence from an emerging economy context - Scaliza, Janaina Aparecida Alves [UNESP]; Jugend, Daniel [UNESP]; Chiappetta Jabbour, Charbel Jose; Latan, Hengky; Armellini, Fabiano; Twigg, David; Andrade, Darly Fernando (Elsevier, 2022)
The exploration and retention of knowledge are key elements for improving innovative performance. Although some studies indicate that organizational culture (OC) is a factor that influences knowledge management in companies, the relationships between different types of OC and the adoption of open innovation (OI) remain unclear, especially in the context of emerging economies such as Brazil. Our study addresses this research gap by investigating the relationships among OC, inbound and outbound OI, innovation ecosystems and innovative performance. With data collected from 169 companies in Brazil, our main results show that adhocracy culture is the type of OC that most influences the adoption of inbound and outbound OI flows, and that hierarchy culture discourages the adoption of OI. Our results also suggest the importance of adopting knowledge management practices that foster creativity and flexibility.
Keywords: Innovation ecosystem; Open business model; Open innovation; Organizational culture